Code of Ethics for Advocates ENFORCEMENT OF THE ADVOCATE PROFESSIONAL CODE OF ETHICS IN CLIENT ASSISTANCE IN CRIMINAL CASES OF CORRUPTION - Siti Zulaiha; Nurul Fahmidab; Fauziah Lubis (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2023)
The profession of an advocate as a law enforcer is based on Law Number 18 of 2003 concerning Advocates and Article 24 Paragraph (1) of the 1945 Constitution. The profession of a free, independent and responsible advocate is regulated in Law Number 18 of 2003. An advocate is a profession that provides legal services, where when carrying out his duties and functions he can act as a companion, give legal opinion or become a legal representative for and on behalf of his client. Advocate profession is inseparable from a code of ethics which contains values ​​and morals. Regarding advocates who are related to corruption cases, the legal services provided to the public by law enforcement officials aim to respect and provide legal protection humanely without distinguishing between the rich and the poor.